Homicides in England and Wales: The Effects of Victim and Offense Characteristics on Case Clearance - Nicholls, Rebecca (Homicide studies, 2025)
This study explores a range of victim and offense characteristics to identify which are associated with significantly higher or lower likelihood of homicide clearance in England and Wales. Data relating to 6,299 currently recorded homicides from the Home Office Homicide Index over an 11-year period (ending March 2022) were analyzed using binary logistic regression to assess the factors which influence the likelihood of clearance. Results indicated greater odds of clearance if the victim was female or if the victim was living with the suspect. Additionally, results indicated lower odds of clearance if the victim was older than 46 years, if the victim was intoxicated with drugs and alcohol, if the method of offense was hitting or kicking without a weapon, poisoning, exposure or negligence, if the main circumstance of the offense was a reckless act, or if the offense was gang-related. We discuss the implications of these findings for future research on homicide clearance, and implications for policy and practice.